All the Colors of the Dark - Whitaker, Chris (New York : Crown, 2024)
"From the New York Times bestselling author of We Begin at the End comes an epic novel about a man fixated on finding a missing woman and the FBI agent on his tail, who might be even more obsessed than he is"--
Keywords: Missing persons -- Fiction; Serial murderers -- Fiction; Missouri -- Fiction; Thrillers (Fiction); Detective and mystery fiction